Discrimination in Health Care: A Scoping Review of the Ontario Experience - DRAZENOVICH, GEORGE (Health and human rights, 2025)
This scoping review examines systemic and direct health care discrimination in Ontario, Canada, from 2021 to 2024, analyzing claims, contexts, affected groups, interventions, and research gaps. It reviews 23 Human Rights Tribunal of Ontario cases, 11 articles, and 5 gray literature reports. Findings highlight prevalent discrimination claims, including denial of service, denial of entitlement, service removal, and reprisal, which disproportionately affect Indigenous Peoples, racialized groups, and individuals with disabilities. Studies emphasized policy and educational interventions, advocating culturally informed practices and rural resource equity. Following the spirit and intent of human rights law, which is preventative and remedial and not punitive, the review recommends several policy reforms, increased representation of marginalized groups, and mediation to address claims. It urges codifying health care as a constitutional right to ensure an inclusive system meeting Ontario’s diverse needs.